A new approach to modeling perpendicular fabrics in porphyritic plutonic rocks using the finite element method - Žák, Jiří; Kabele, Petr (International journal of earth sciences : Geologische Rundschau, 2012)
A growing body of field evidence indicates that hypersolidus fabrics preserved in syntectonic plutons are likely to have formed in highly crystallized ‘rigid sponge’ magma. This paper demonstrates that such magma could be idealized as a rheological solid and that the development of non-coaxial fabrics in plutonic rocks can very conveniently be modeled in the framework of solid mechanics. Using the finite element method (FEM), we modeled two strain regimes of small magnitudes (plane-strain horizontal simple shear with the shear strain γ of up to 0.30 and plane-strain pure shear of up to 15% shortening) superposed onto vertically oriented and variously spaced elastic phenocrysts set in the viscoelastic matrix. In the simple shear regime, the phenocrysts slightly rotate toward the shear plane, while the principal strain directions in the matrix are instantaneously oriented at an angle of about 45° or less to the phenocryst fabric. Simple shear thus can only lead to the formation of oblique phenocryst and matrix fabrics. By contrast, the vertical phenocryst fabric is maintained in the pure shear regime, and a new horizontal fabric can develop almost instantaneously in the matrix even for small amounts of superposed shortening (5% shortening after 10 ky in our model). We conclude that such a mechanism can easily produce perpendicular hypersolidus fabrics in plutonic rocks and that only a very short time span (first thousands of years) is required to develop magmatic fabric in a pluton for ‘normal’ rates (10 −15 to 10 −13 s −1 ) of tectonic deformation.